Digital Marketing Biro Haji Umroh Dalam Merekrut Jamaah Sebelum Dan Disaat Pandemi - Umi Latifah; Burhanudin AY; Istiqomah Istiqomah (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to analyze the digital marketing strategy of the Hajj and Umrah bureau in recruiting pilgrims before and during the pandemic, as well to find out the differences in digital marketing strategies. The object of research at PT. Amanau Izzah Zamzam Sakinah Surakarta. The research method with qualitative uses primary data and secondary data. Research informants are leaders, marketing staff, digital marketing staff. Data collection techniques with interviews, observation, and documentation. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The result is that the digital marketing strategies used before the pandemic were websites, Facebook, Instagram, Pinterest and WhatsApp. during a pandemic, focus on digital marketing such as websites, Facebook, and WhatsApp. The difference in the focus of the three social media is seen from the large number of registrants from the website, Facebook, and WhatsApp so that currently they are maximizing it